Assessment Framework for People-Centred Solutions to Carbon Neutrality A Comprehensive List of Case Studies and Social Innovation Indicators at Urban Level - Bresciani, Sabrina; Rizzo, Francesca; Mureddu, Francesco; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access book presents a catalogue of over one thousand indicators which can be used by cities' public administrators to monitor and evaluate social innovation action plans to support people-centred, collaborative or co-designed solutions to lower carbon emissions. Indicators are clustered according to a framework of social innovation solutions for climate neutrality at city level, developed by merging top-down academic knowledge with bottom-up pragmatic case studies. There is currently limited guidance on how to embed social innovations in their cities$1 (Baction plans with the aim of reaching climate neutrality, and on how to assess the progress and impacts of such people-centred projects in cities. The book addresses this gap and is thus relevant for scholars in the field of policy-making and design, as well as cities$1 (Btransition teams, policymakers and consultants. Based on the work developed within the EU-funded project NetZeroCities, intervention logics are provided for each of the ten categories of action, with related indicators clustered by category and evaluation criteria (effectiveness, efficiency, relevance, replicability, and scalability). Guidelines to implement the framework support city administrators in defining steps they need to follow to apply the indicators to their local case, making social innovation a crucial lever for accelerating systemic transformation. .s
Social Innovation and co-design for climate neutrality: The NetZeroCities project -- Impact Logic: Social Innovation Categories for Cities$1 (BAction Plans -- Indicators of Social Innovation for Cities$1 (BAction Plans Evaluation -- Applying the Indicators in Cities.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Sustainability; Technological innovations; Climatology; Sociology, Urban; Sustainability; Innovation and Technology Management; Climate Sciences; Urban Sociology